Analysis of the construction of a reinforced-concrete free-form roof formwork and the development of a unit-construction method. (February 2021) - Hayashi, Sei; Gondo, Tomoyuki
Abstract: Since the advent of the modernist movement in architecture, organic shapes have attracted designers. Digital fabrication technology and three-dimensional computer-aided design have made the architectural design of free-form shapes much easier. However, the construction of these shapes still has many risks in terms of cost and time management. This study aims to develop a new unit construction method by integrating digital fabrication with the conventional wooden construction technique on a large architectural scale and compare its productivity throughout the construction process to the conventional method. This paper first illustrates the current situation of free-form shape production by surveying a reinforced-concrete roof-construction project using a conventional construction method in Japan. We then develop a new construction method in which curved surfaces are divided into portable units in order to reduce on-site labor and ensure a high degree of accuracy. Finally, we analyze its productivity by conducting some assembly experiments. The new method reduces on-site labor costs by 93% compared with the conventional method. Highlights: Elucidate a freeform-roof-construction using a conventional method. Develop new methods to construct curved surface in order to reducing on-site labor. Analyze the productivity of new method and it reduces labor costs by 93%.